Mutu kulit jaket dari kulit domba peranakan merino - Oetojo, Bambang; Lutfi, Muchtar; Widari, Widari; Basalamah, Hasan (Majalah Kulit, Karet, dan Plastik, 1990)
To compare the quality of jacket leather output from merino descendent sheep skin to that one yield from local sheep skin is the purpose of this research. For this comparative research it was used four pieces of good quality merino descendent sheep skin and four pieces of good quality local sheep skin. Through the ordinary tanning method, all of the skins, either merino descendent sheep skins or the local one were process into jacket leather. Further more the jacket leathers output from this research were visual investigeted and physical tested. Statistical analysis points out that there is unsignify difference (P â¼ 0,05) the influence of the spesies either it is merino descendent sheep skin or the local one to the tensile strenght and the stretch of jacket leather. It is also unsignify difference (P â¼ 0,05) the influence of the spesies either it is merino descendent sheep skin or the local one to the quality of jacket leather.Practical meaning of this research is that merino descendent sheep skin may be tanned into jacket leather having same quality to that one from local sheep skin.Â